Cardiovascular risk in educators of healthcare professionals. Universidad Técnica del Norte, Ibarra, 2021-2022 - Jorge Gabriel Ponce Ruiz; Adriana Edit Miniet Castillo; Jorge Luis Anaya Gonzalez; Alicia Salome Gordillo Alarcón (Universidad de Ciencias Médicas de La Habana, 2023)
Introduction: Cardiovascular diseases are the main cause of death in the world, causing 2 million deaths annually; 80 % of them in low- or middle-income countries. Objective: To relate the level of cardiovascular risk, profession, and labor duality in professors from the Faculty of Health Sciences, Universidad Técnica del Norte, Ibarra, 2021-2022. Material and Methods: Non-experimental, relational, cross-sectional study, whose universe consisted of 96 professors from the Faculty of Health Sciences of the Universidad Técnica del Norte. The individual levels of RCVC, which were obtained through the Framingham risk assessment scale adapted from REGICOR, were estimated; a descriptive analysis of the variables was carried out; mean, standard deviation, as well as frequencies and percentages were applied in the qualitative ones. The association between variables was evaluated using the chi-square statistical test, with 95 % confidence interval and a p value ≤ 0.05. Results: The female sex (79.2 %) and labor duality (57.3 %) prevailed among the professors studied; the average of total cholesterol exceeded the desired limits (202.57 mg/dl), HDL cholesterol prevailed with values lower than normal and the low level of cardiovascular risk prevailed. Conclusions: It was demonstrated that there is a statistically significant association between the level of cardiovascular risk and the profession of the educators from the Faculty of Health Sciences, Universidad Técnica del Norte, Ibarra. The difference in the number of professors with a low and medium level of cardiovascular risk was greater among those who practice labor duality.